Method for manufacturing paper with high filler content

By adding titanium dioxide filler and amphoteric polyacrylamide to the pulp slurry, the problems of filler aggregation and low production efficiency in high filler content paper are solved, and paper products with high ash content and high opacity are achieved, reducing costs and environmental load.

CN120174659APending Publication Date: 2025-06-20KURITA WATER INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510481199.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-12-04
Filing Date
2021-11-24
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

When the prior art improves the opacity and ash content of paper with high filler content, there are problems such as filler aggregation, reduced production efficiency and decreased paper quality, especially the high cost of titanium dioxide and easy to cause pollution.

Method used

By adding filler containing a predetermined amount of titanium dioxide to the pulp slurry and adding amphoteric polyacrylamide on this basis, the filler is evenly dispersed and fixed in the pulp fibers, the proportion of filler flowing out to the white water system is reduced.

Benefits of technology

A paper product with high ash content and high opacity is achieved, while reducing filler usage and production costs, reducing equipment pollution and environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120174659A_ABST
    Figure CN120174659A_ABST
Patent Text Reader

Abstract

The invention provides a method for manufacturing paper with high filler content. The method for producing paper having a high filler content comprises: a paper stock production step (S1) in which a filler containing titanium dioxide is added to a pulp slurry to obtain a paper stock; an amphoteric polyacrylamide addition step (S2) in which an amphoteric polyacrylamide is added to the paper material in a range of 0.005-3 mass% with respect to the total mass of the solid content of the pulp fibers and the filler; and a papermaking step (S3) for papermaking the paper material to which the amphoteric polyacrylamide has been added, in which the content of titanium dioxide in the paper material obtained in the paper material production step (S1) is 1 mass% or more relative to the total mass of the solid content of the pulp fibers and the filler, and the content of titanium dioxide in the paper material obtained in the paper material production step (S1) is 1 mass% or more relative to the total mass of the solid content of the filler. And the content of the filler containing titanium dioxide is in the range of 8.5 mass% to 50 mass% (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of November 24, 2021, an application number of 202180076254.X, and an invention title of "Method for manufacturing paper with high filler content". Technical Field

[0002] The present invention relates to a method for manufacturing paper with high filler content, and particularly to a method for manufacturing paper with high filler content that requires high opacity. Background Art

[0003] In recent years, from the viewpoints of resource conservation and waste reduction, lightweight and low basis weight of paper have been desired, and as such paper, filled paper containing a filler is known.

[0004] Filled paper particularly strongly requires improvement in optical properties such as opacity and whiteness even if it is lightweight and has a low basis weight. For example, for building material paper such as base paper for decorative boards, high opacity is required so that the base material part cannot be seen when laminated on the base material. In addition, dictionary paper used for dictionaries etc. also requires high opacity, and it is important that characters or figures cannot be seen from the back.

[0005] Here, as a method for improving optical properties such as opacity and whiteness, a method of adding papermaking fillers such as titanium dioxide and calcium carbonate to pulp has been used. In particular, since titanium dioxide has a high light scattering ability, it can impart high opacity to paper. However, since titanium dioxide has a smaller particle size than other papermaking fillers, its retention during papermaking using a paper machine is extremely low, and thus titanium dioxide easily accumulates and contaminates in the paper machine and its attached devices. Therefore, in the method of adding titanium dioxide to pulp, there is a problem of reduced production efficiency due to the high frequency of cleaning the paper machine. In addition, in this method, there is also a problem of reduced paper quality due to the accumulation and contamination of titanium dioxide being incorporated into the paper.

[0006] Furthermore, even when using a filler other than titanium dioxide, such as light calcium carbonate, when the ratio of the filler in the paper is increased for the purpose of improving opacity, the filler that is not fixed in the paper and flows out to the white water system also increases. Therefore, similar to the case of adding titanium dioxide to pulp, there are problems of reduced production efficiency and reduced paper quality.

[0007] Therefore, in order to improve the retention of fillers, a method of adding a retention aid together with the filler to the pulp has been continuously adopted. As a method of adding a retention aid to the pulp, for example, the following methods can be cited: a method of adding a cationic or anionic polyacrylamide alone to the pulp; a method of adding an anionic polyacrylamide after adding a cationic polyacrylamide; a method using two components of adding a colloidal silica, bentonite, etc. as an anionic agent after adding a cationic polymer; a method using three components of adding a cationic coagulant before the method using two components; a method using three components of adding an anionic polymer after adding a cationic polymer and then adding an anionic agent.

[0008] For example, Patent Document 1 describes a method in which carboxymethyl cellulose having a degree of substitution of 0.3 to 0.6 is added to a cellulose fiber slurry (pulp slurry), and then aluminum sulfate and titanium dioxide are added and papermaking is performed.

[0009] In addition, Patent Document 2 describes a method in which an amphoteric water-soluble polymer is added to a furnish (pulp slurry), the amphoteric water-soluble polymer is produced by dispersion polymerization in an aqueous salt solution and the monomer contains acrylamide, and then an anionic colloidal silica and bentonite are added.

[0010] In addition, Patent Document 3 describes a method in which a polymer and titanium dioxide or calcium carbonate are added to a pulp slurry, and the polymer is obtained by hydrolyzing 20 to 100% of the total formyl groups in a polymer having at least N-vinylformamide as a polymerization component.

[0011] Prior Art Documents

[0012] Patent Documents

[0013] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2003-89994

[0014] Patent Document 2: Japanese Unexamined Patent Application Publication No. 9-195197

[0015] Patent Document 3: Japanese Unexamined Patent Application Publication No. 2005-171411 Summary of the Invention

[0016] Problems to be Solved by the Invention

[0017] However, in these methods, although the retention of the filler is improved, the following problems exist: due to the aggregation of the filler, even if the addition amount of the filler is increased, the opacity of the resulting paper will decrease. In addition, titanium dioxide added as a filler is very expensive, so the raw material cost of titanium dioxide accounts for a large proportion of the cost in papermaking. In particular, in the existing methods of adding a retention aid, even if the addition amount of titanium dioxide is increased, the opacity of the paper cannot be increased. Therefore, the method of adding a large amount of titanium dioxide is not ideal.

[0018] In contrast, in the method described in Patent Document 1, since carboxymethyl cellulose is suspended in the pulp slurry, agglomerates formed by the adhesion of hydrated powder particles, i.e., lumps, are likely to be generated in large quantities in the pulp slurry. In addition, the method of Patent Document 1 makes it difficult to efficiently fix the filler to the pulp fibers, and since it is used to obtain thick paper, there is room for improvement in terms of increasing the ash content rate and opacity even when the resulting paper is thin.

[0019] In addition, in the method described in Patent Document 2, the retention rate of the filler is improved by adding anionic colloidal silica and bentonite as retention improvers to the pulp slurry. However, since the addition amount of the filler is small, the ash content rate and opacity of the resulting paper are also low.

[0020] In addition, in the method described in Patent Document 3, in order to obtain a paper with a high ash content rate and opacity, it is necessary to increase the raw material cost to increase the relative amount of titanium dioxide as a filler relative to the pulp fibers. In addition, in Patent Document 3, since the outflow ratio (amount) of the filler that is not fixed in the paper and flows out to the white water system when the use amount of fillers such as titanium dioxide is increased is not considered, it does not describe minimizing the amount of the filler flowing out to the white water system to prevent the accumulation or contamination of titanium dioxide in the paper machine and its auxiliary devices.

[0021] The present invention has been completed in view of the above actual situations, and its object is to provide a method for manufacturing a paper with a high filler content, which can obtain a paper with a high ash content rate and high opacity by preventing the aggregation of the filler and fixing it to the pulp fibers in as uniform a dispersed state as possible, and reducing the outflow ratio (amount) of the filler flowing out to the white water system. Moreover, the outflow ratio of the filler flowing out into the white water is small.

[0022] Solutions for Solving the Problems

[0023] The inventor of the present invention has conducted repeated and in-depth research to solve the above technical problems. As a result, it has been found that according to the manufacturing method of paper with a high filler content, the manufacturing method includes: a stock preparation step of adding a filler containing a specified amount of titanium dioxide to a pulp slurry to obtain a furnish; and an amphoteric polyacrylamide addition step of adding a specified amount of amphoteric polyacrylamide to the furnish. The filler is fixed to the pulp fibers in a uniformly dispersed state, and the outflow ratio (amount) of the filler flowing out into the white water system is reduced. Therefore, paper with a high ash content and high opacity can be obtained, and the outflow ratio of the filler flowing out into the white water can be reduced, thus completing the present invention. Specifically, the present invention provides the following.

[0024] (1) A manufacturing method of paper with a high filler content, which includes: a stock preparation step of adding a filler containing titanium dioxide to a pulp slurry to obtain a furnish; an amphoteric polyacrylamide addition step of adding amphoteric polyacrylamide to the aforesaid furnish in a range of 0.005% by mass or more and 3% by mass or less based on the total mass of the solid components of the pulp fibers and the aforesaid filler; and a papermaking step of papermaking the furnish to which the aforesaid amphoteric polyacrylamide has been added, wherein, in the aforesaid furnish obtained by the aforesaid stock preparation step, the content rate of the aforesaid titanium dioxide is 1% by mass or more based on the total mass of the solid components of the aforesaid pulp fibers and the aforesaid filler, and the content rate of the aforesaid filler containing the aforesaid titanium dioxide is in a range of 8.5% by mass or more and 50% by mass or less.

[0025] (2) The manufacturing method of paper with a high filler content according to the above (1), wherein, in the aforesaid stock preparation step, aluminum sulfate is further added in a range of 0.5% by mass or more and 10% by mass or less based on the total mass of the solid components of the aforesaid pulp fibers and the aforesaid filler.

[0026] (3) The manufacturing method of paper with a high filler content according to the above (1) or (2), which further includes, before the amphoteric polyacrylamide addition step: an amphoteric polyacrylamide production step of polymerizing monomers in an aqueous medium to produce the aforesaid amphoteric polyacrylamide, wherein the aforesaid monomers contain, relative to the total molar sum: (meth)acrylamide in a range of 60 mol% or more and 98 mol% or less, an anionic vinyl monomer in a range of 1 mol% or more and 39 mol% or less, and a cationic vinyl monomer in a range of 1 mol% or more and 39 mol% or less.

[0027] (4) The manufacturing method of paper with a high filler content according to any one of the above (1) to (3), wherein the Brookfield viscosity of the aforesaid amphoteric polyacrylamide produced by the aforesaid amphoteric polyacrylamide production step is in a range of 1000 cps or more and 20000 cps or less when the solid component concentration is set to 10% by mass.

[0028] (5) The method for manufacturing a paper with a high filler content according to any one of the above (1) to (4), wherein the ash content of the paper with the high filler content is in the range of 8.5% by mass or more and 50% by mass or less.

[0029] Effects of the Invention

[0030] According to the present invention, a method for manufacturing a paper with a high filler content can be provided, which can fix the filler added to the pulp slurry in a relatively uniform dispersion state with respect to the pulp fibers. Therefore, even if the amount of filler added is reduced, a paper with a high ash content and high opacity can be obtained, and moreover, the outflow ratio of the filler flowing into the white water is small.

[0031] In particular, in the present invention, since the filler can be efficiently fixed to the pulp fibers, the amount of filler used in manufacturing a paper with a high filler content can be reduced. At the same time, the outflow ratio of the filler flowing into the white water is reduced, thereby reducing the contamination of the paper machine and auxiliary equipment caused by the filler not fixed to the pulp fibers. Therefore, a method for manufacturing a paper with a high filler content that can reduce the environmental load and economic load can be provided.

[0032] Moreover, in the manufacturing method of the present invention, fillers such as titanium dioxide and calcium carbonate in the furnish during papermaking do not aggregate excessively, but are fixed to the pulp fibers in a relatively uniform dispersion state. Therefore, a paper with a high filler content having good physical properties such as high opacity and whiteness can be obtained, and it can be applied to uses such as base paper for building materials and bible paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a flowchart showing an example of the method for manufacturing a paper with a high filler content of the present invention.

[0034] Figure 2 (a) is a schematic diagram for explaining the dispersion state of the filler in the furnish in the method for manufacturing a paper with a high filler content of the present invention, Figure 2 (b) is a schematic diagram for explaining the dispersion state of the filler in the furnish in the conventional manufacturing method. DETAILED DESCRIPTION OF THE INVENTION

[0035] Hereinafter, the specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments, and can be appropriately modified and implemented within the scope of the object of the present invention.

[0036] <Manufacturing method of paper with high filler content>

[0037] As Figure 1As shown in the flowchart, the method for manufacturing a paper with a high filler content according to the present invention includes: a stock preparation step S1 of obtaining a furnish by adding a filler containing titanium dioxide to a pulp slurry; an amphoteric polyacrylamide addition step S2 of adding an amphoteric polyacrylamide to the furnish; and a papermaking step S3 of making paper from the furnish to which the amphoteric polyacrylamide has been added. Among them, in the furnish obtained in the stock preparation step S1, the content rate of titanium dioxide is 1% by mass or more with respect to the total mass of the solid components of the pulp fibers and the filler, and the content rate of the filler containing titanium dioxide is in the range of 8.5% by mass or more and 50% by mass or less. In addition, the addition amount of the amphoteric polyacrylamide in the amphoteric polyacrylamide addition step S2 is in the range of 0.005% by mass or more and 3% by mass or less with respect to the total mass of the solid components of the pulp fibers and the filler. In particular, the addition amount of the amphoteric polyacrylamide with respect to the furnish is preferably in the range of 0.01% by mass or more and 1% by mass or less, more preferably in the range of 0.015% by mass or more and 0.5% by mass or less, with respect to the total mass of the solid components of the pulp fibers and the filler.

[0038] In the manufacturing method of the present invention, as Figure 2 shown in (a) of, in the furnish 1 after adding the amphoteric polyacrylamide 2, fillers 3 such as titanium dioxide and calcium carbonate are fixed to the pulp fibers 4 in a dispersed state rather than being overly aggregated, and less filler 3 flows out into the white water system. In contrast, in the furnish 9 of the conventional method, as Figure 2 shown in (b) of, the filler 3 aggregates due to the retention aid 5, and the aggregates adhere to the pulp fibers 4. Therefore, in the manufacturing method of the present invention, the filler 3 is less likely to aggregate on a partial surface of the pulp fibers 4, and less filler 3 flows out into the white water system, so that the ash content rate and opacity of the obtained paper with a high filler content can be improved.

[0039] (Pulp fibers)

[0040] The pulp fibers 4 used in the manufacturing method of the present invention are not particularly limited, and may be so-called virgin pulps such as chemical pulp (also called "kraft pulp") and mechanical pulp, or waste paper such as manufacturing residues (broken paper) and recycled waste paper in the papermaking process. These pulp fibers 4 are suspended in water to form a pulp slurry.

[0041] (Stock preparation step S1)

[0042] The stock preparation step S1 is a step of obtaining a furnish by adding a filler 3 containing titanium dioxide to a pulp slurry. Thereby, a furnish containing pulp fibers 4 and a filler 3 can be formed.

[0043] The filler 3 is an additive as ash in the resulting paper with a high filler content. As the filler 3, from the viewpoint of obtaining a high opacity, it contains at least titanium dioxide. In addition, as the filler 3, in addition to titanium dioxide, it may also contain inorganic compounds commonly used as paper fillers, namely, precipitated calcium carbonate, ground calcium carbonate, kaolin, talc, clay, precipitated silica, aluminum hydroxide, etc. It should be noted that the filler 3 may also contain fillers derived from waste paper.

[0044] In the papermaking stock preparation step S1, the filler 3 is added in such a manner that the content rate of titanium dioxide in the papermaking stock reaches 1% by mass or more with respect to the total mass of the solid components of the pulp fibers 4 and the filler 3. In addition, the filler 3 is added in such a manner that the content rate of ash such as titanium dioxide, clay, and calcium carbonate in the resulting paper with a high filler content reaches a range of 8.5% by mass or more and 50% by mass or less. Thus, by including titanium dioxide with high light-scattering ability as the filler 3 in the papermaking stock, the titanium dioxide can be fixed to the pulp fibers 4, and therefore, a high opacity can be imparted to the paper with a high filler content. On the other hand, the upper limit of the content rate of titanium dioxide in the papermaking stock is not particularly limited and can be set to 50% by mass or less with respect to the total mass of the solid components of the pulp fibers and the filler.

[0045] As the titanium dioxide added in the papermaking stock preparation step S1, anatase type or rutile type can be arbitrarily used. In addition, titanium dioxide coated with alumina or silica can also be used. In addition, when adding titanium dioxide to the papermaking stock, titanium dioxide in a slurry state dispersed in water can be used, or a dispersant such as sodium polyacrylate can be used in order to obtain a uniformly dispersed slurry state of titanium dioxide, and these dispersants may not be used.

[0046] In addition, in the papermaking stock preparation step S1, the filler 3 is added in such a manner that the content rate of the filler 3 containing titanium dioxide in the papermaking stock reaches a range of 8.5% by mass or more and 50% by mass or less with respect to the total mass of the solid components of the pulp fibers 4 and the filler 3. Among them, by making the content rate of the filler 3 8.5% by mass or more with respect to the total mass of the solid components of the pulp fibers 4 and the filler 3, it is possible to easily obtain a paper with a high filler content having a desired high opacity. Therefore, it is preferable that the content rate of the filler 3 is more than 10% by mass, more preferably more than 20% by mass or more, and further preferably more than 35% by mass with respect to the total mass of the solid components of the pulp fibers 4 and the filler 3. On the other hand, by making the content rate of the filler 3 50% by mass or less with respect to the total mass of the solid components of the pulp fibers 4 and the filler 3, it is possible to suppress a decrease in strength and printability and an increase in raw material cost due to excessive inclusion of the filler 3.

[0047] In addition, in the furnish preparation step S1, it is preferable to add aluminum sulfate to the pulp slurry in a range of 0.5% by mass or more and 10% by mass or less based on the total solid content mass of the pulp fibers 4 and the filler 3 after adding the filler 3 containing titanium dioxide to the pulp slurry. Thereby, the fixation of the filler 3 to the pulp fibers 4 can be promoted.

[0048] In addition, in the furnish preparation step S1, after adding the filler 3 containing titanium dioxide to the pulp slurry, polyamine polyamide type as a wet strength agent; ASA, AKD, rosin solution / emulsion as a sizing agent; polyethyleneimine, polyDADMAC, polyamine epichlorohydrin resin, cationic polyacrylamide, etc. as a cationic charge regulator can also be added to the pulp slurry. In addition, as other chemicals, aluminum compounds such as polyaluminum chloride and sodium aluminate, natural / synthetic paper strength enhancers, dispersants, dyes, pigments, defoamers, or pH regulators, etc. can also be added to the pulp slurry.

[0049] It should be noted that aluminum sulfate; wet strength agents, sizing agents, cationic charge regulators, aluminum compounds; natural / synthetic paper strength enhancers, dispersants, dyes, pigments, defoamers, pH regulators, etc. can also be added to the furnish after the amphoteric polyacrylamide addition step S2 described below.

[0050] (Amphoteric polyacrylamide addition step S2)

[0051] The amphoteric polyacrylamide addition step S2 is a step of adding amphoteric polyacrylamide 2 to the furnish in a range of 0.005% by mass or more and 3% by mass or less based on the total solid content mass of the pulp fibers and the filler 3.

[0052] As the amphoteric polyacrylamide 2, a copolymer polymerized in the form of monomers containing (a) (meth)acrylamide, (b) an anionic vinyl monomer, and (c) a cationic vinyl monomer can be used. In the amphoteric polyacrylamide 2 containing such a copolymer, anionic functional groups and cationic functional groups are mixed and present in the same molecule, so they interact with each other and react with fillers 3 such as titanium, whereby the fillers 3 and the amphoteric polyacrylamide 2 are dispersed and do not aggregate excessively, and are easily fixed on the surface of the pulp fibers 4. Therefore, the opacity of the paper with a high filler content can be improved. In addition, the fixation of the filler 3 on the surface of the pulp fibers 4 is promoted, so that the ash content rate of the paper with a high filler content can be increased, and the concentration of the filler 3 in the white water can be effectively reduced. As a result, the mechanical pollution from the white water can be reduced, and the drainage effect, etc. can also be improved, and furthermore, the productivity such as the machine speed can be increased.

[0053] Among them, (a) (meth)acrylamide in the monomer is acrylamide or methacrylamide, and at least one of these can be used as a monomer. In particular, from the viewpoint of suppressing raw material costs, it is preferable to use acrylamide as the monomer. It should be noted that the meaning of "(meth)" in this specification is: including both substances having the expression "methyl" (for example, methacryloyl) and substances not having the expression "methyl" (for example, acryloyl).

[0054] The content of (a) acrylamide in the amphoteric polyacrylamide 2 is in the range of 60 mol% or more and 98 mol% or less, preferably in the range of 70 mol% or more and 94 mol% or less, more preferably in the range of 80 mol% or more and 90 mol% or less, relative to the total molar sum of the constituent monomers. Among them, by increasing the content of (a) acrylamide, the filler 3, particularly titanium oxide, can be fixed to the pulp fiber 4, and thus the effect of improving opacity can be easily obtained.

[0055] In addition, examples of the (b) anionic vinyl monomer include: α,β-unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and (meth)allyl carboxylic acid; α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and muconic acid; organic sulfonic acids such as vinylsulfonic acid, styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and (meth)allylsulfonic acid; and alkali metal salts such as sodium salts and potassium salts of these various organic acids, or ammonium salts. As the (b) anionic vinyl monomer, one or more of these compounds can be used. Among them, as the (b) anionic vinyl monomer, it is preferable to use acrylic acid or itaconic acid.

[0056] The content of the (b) anionic vinyl monomer in the amphoteric polyacrylamide 2 is in the range of 1 mol% or more and 39 mol% or less, preferably in the range of 3 mol% or more and 27 mol% or less, more preferably in the range of 2 mol% or more and 18 mol% or less, relative to the total molar sum of the constituent monomers.

[0057] In addition, examples of the (c) cationic vinyl monomer include: vinyl monomers having a tertiary amino group such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylamide, and diethylaminopropyl (meth)acrylamide, and their salts with hydrochloric acid, sulfuric acid, acetic acid, and organic acids; and vinyl monomers containing a quaternary ammonium salt obtained by the reaction of the vinyl monomer having a tertiary amino group with a quaternizing agent such as methyl chloride, benzyl chloride, dimethyl sulfate, and epichlorohydrin.

[0058] The content of the (c) cationic vinyl monomer in the amphoteric polyacrylamide 2 is in the range of 1 mol% or more and 39 mol% or less, preferably in the range of 3 mol% or more and 27 mol% or less, and more preferably in the range of 2 mol% or more and 18 mol% or less, relative to the total molar sum of the constituent monomers.

[0059] Among them, the molar ratio of the content of the (b) anionic vinyl monomer to the content of the (c) cationic vinyl monomer is preferably in the range of 0.1 or more and 39 or less, more preferably in the range of 0.1 or more and 20 or less, and further preferably in the range of 0.1 or more and 10 or less. By setting the molar ratio within the above range, the filler 3 can be fixed on the surface of the pulp fiber 4 in a more dispersed state.

[0060] In the amphoteric polyacrylamide 2, in addition to the (a) (meth)acrylamide, (b) anionic vinyl monomer, and (c) cationic vinyl monomer, the monomers may further include N-substituted (meth)acrylamides represented by the following general formula (I) and / or polyfunctional monomers.

[0061] CH2=C(R 1 )-CONR 2 (R 3 )…Formula (I)

[0062] (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms, and R 3 is a linear or branched alkyl group having 1 to 4 carbon atoms.)

[0063] Among them, since the methyl group and methylene group in the N-alkyl of the N-substituted (meth)acrylamides represented by the general formula (I) act as chain transfer points, a large number of branched structures can be introduced into the amphoteric polyacrylamide 2, and thus a branched polymer can be obtained without gelation.

[0064] In the general formula (I), as the linear or branched alkyl group having 1 to 4 carbon atoms in R 2 or R 3 , examples include: methyl group, ethyl group, isopropyl group, tert-butyl group, etc. In addition, as specific examples of the N-substituted (meth)acrylamides, examples include: N,N-dimethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-tert-butyl(meth)acrylamide. Among these, from the viewpoints of copolymerizability and chain transferability, N,N-dimethylacrylamide is preferred.

[0065] In addition, a crosslinked structure can also be imparted to the amphoteric polyacrylamide 2 by using a polyfunctional monomer. Among them, examples of the polyfunctional monomer include: di(meth)acrylate such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, and triethylene glycol di(meth)acrylate; bis(meth)acrylamide such as methylene bis(meth)acrylamide, ethylene bis(meth)acrylamide, and hexamethylene bis(meth)acrylamide; divinyl esters such as divinyl adipate and divinyl sebacate; bifunctional vinyl monomers such as allyl methacrylate, diallylamine, diallyldimethylammonium, diallyl phthalate, diallyl chlorendate, divinylbenzene, and N,N-diallylacrylamide; trifunctional vinyl monomers such as 1,3,5-triacryloylhexahydro-s-triazine, triallyl isocyanurate, triallylamine, and triallyl trimellitate; tetrafunctional vinyl monomers such as tetramethylolmethane tetraacrylate, tetraallyl pyromellitate, N,N,N',N'-tetraallyl-1,4-diaminobutane, tetraallyl ammonium salt, and tetraallyloxyethane; and N-hydroxymethylacrylamide. Among these polyfunctional monomers, 1,3,5-triacryloylhexahydro-s-triazine, triallyl isocyanurate, etc. are preferably used.

[0066] The contents of the N-substituted (meth)acrylamide and polyfunctional monomer represented by the general formula (I) in the amphoteric polyacrylamide 2 are preferably 10 mol% or less, more preferably 5 mol% or less, respectively, based on the total molar sum of the constituent monomers. On the other hand, from the viewpoint of exerting the function of the N-substituted (meth)acrylamide, the lower limit of the content of the N-substituted (meth)acrylamide represented by the general formula (I) is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, based on the total molar sum of the constituent monomers.

[0067] Furthermore, in the monomers of the amphoteric polyacrylamide 2, in order to impart hydrophobicity, nonionic vinyl monomers such as alkyl esters (alkyl having 1 to 8 carbon atoms) of the same monomers as the (b) anionic vinyl monomer, acrylonitrile, styrene-based compounds, vinyl acetate, and methyl vinyl ether can be contained. Among them, when the nonionic vinyl monomer is contained, the content is preferably 30 mol% or less, more preferably 20 mol% or less, based on the total molar sum of the constituent monomers.

[0068] The amphoteric polyacrylamide 2 is preferably produced by an amphoteric polyacrylamide production step S11 in which these monomers are copolymerized in an aqueous medium before the amphoteric polyacrylamide addition step S2. Among them, the amphoteric polyacrylamide production step S11 can be carried out immediately before the amphoteric polyacrylamide addition step S2. In addition, based on the amphoteric polyacrylamide 2 obtained by previously carrying out the amphoteric polyacrylamide production step S11, the amphoteric polyacrylamide 2 can be used in the amphoteric polyacrylamide addition step S2.

[0069] In the amphoteric polyacrylamide production process S11, as a copolymerization method for producing the amphoteric polyacrylamide 2 by polymerizing these monomers, a known radical polymerization method can be used, and bulk polymerization, aqueous solution precipitation polymerization, suspension polymerization, and emulsion polymerization can be arbitrarily used. Among them, when the monomers are polymerized in a solution containing an aqueous medium (solvent), the concentration of the monomers in the solution is preferably in the range of 5% by mass or more and 80% by mass or less, and more preferably in the range of 5% by mass or more and 40% by mass or less.

[0070] In addition, in the amphoteric polyacrylamide production process S11, a known radical polymerization initiator can be used as the polymerization initiator for polymerizing the monomers. As the radical polymerization initiator, ammonium persulfate salts, etc. can be exemplified, but azo compounds can also be used as the radical polymerization initiator. In addition, the polymerization reaction is usually carried out under a non-active gas stream and in a temperature range of 30°C or more and 100°C or less. The obtained copolymer can be in its original state or diluted with an aqueous medium (solvent) such as water or alcohols as needed to form a solution state.

[0071] The Brookfield viscosity of the amphoteric polyacrylamide 2 produced by the amphoteric polyacrylamide production process S11 at a solid content concentration of 10% by mass is preferably in the range of 1000 cps or more and 20000 cps or less. Thus, the filler 3 and the amphoteric polyacrylamide 2 are easily dispersed, and therefore the opacity of the paper with a high filler content can be further improved.

[0072] In the amphoteric polyacrylamide addition process S2, the amphoteric polyacrylamide 2 is added in an amount in the range of 0.005% by mass or more and 3% by mass or less, preferably in the range of 0.01% by mass or more and 1% by mass or less, based on the total solid content mass of the pulp fibers and the filler 3. Thereby, the dispersion of the filler 3 and the fixation to the pulp fibers 4 can be promoted.

[0073] In addition, in the amphoteric polyacrylamide addition process S2, a retention aid improver other than the amphoteric polyacrylamide 2 can be added to the furnish. Examples of such retention aid improvers include: anionic high molecular weight polyacrylamide, cationic high molecular weight polyacrylamide, amphoteric high molecular weight polyacrylamide, silica sol, and bentonite, etc. In addition, one of these retention aid improvers can be used alone, or two or more retention aid improvers can be used in combination.

[0074] The pH of the furnish after the amphoteric polyacrylamide addition process S2 can be set, for example, in the range of 4 or more and 9 or less.

[0075] (Paper-making process S3)

[0076] The papermaking step S3 is a step of making paper from the furnish to which the amphoteric polyacrylamide 2 is added. Thereby, a high filler content paper having a high ash content and a high opacity can be obtained.

[0077] In the papermaking step S3, a known method can be adopted. However, from the viewpoint of suppressing the generation of flocs (lumps) in the furnish, it is preferable to perform papermaking immediately after the above-mentioned amphoteric polyacrylamide addition step S2. Among them, more preferably, after performing the above-mentioned amphoteric polyacrylamide addition step S2 at a position close to the papermaking wire part of the papermaking system, papermaking is performed immediately. In particular, from the viewpoints of improving the drainage property and the paper strength effect of the high filler content paper, it is more preferable to perform the above-mentioned amphoteric polyacrylamide addition step S2 using the blower suction port of the papermaking system.

[0078] (High filler content paper)

[0079] The high filler content paper obtained by the manufacturing method of the present invention has a high ash content and a high opacity. Among them, the ash content and the opacity will have different values depending on the type of the desired high filler content paper product.

[0080] The high filler content paper obtained by the manufacturing method of the present invention mostly has a range of ash content (ash content in paper) of 8.5% by mass or more and 50% by mass or less, typically in the range of 18% by mass or more and 50% by mass or less. Among them, as the ash, the same compounds as the above-mentioned filler 3 can be cited. The manufacturing method of the present invention can obtain a high filler content paper having a high opacity and whiteness within such a wide range of ash content in paper. In particular, even when the ash content in paper is high, the manufacturing method of the present invention can obtain a high filler content paper in which the ash is fixed to the pulp fibers in a dispersed state, and thus can bring good physical properties such as high opacity and whiteness.

[0081] In addition, for the high filler content paper obtained by the manufacturing method of the present invention, the higher the content rate of the filler 3 in the furnish, the higher the opacity tends to be. Among them, the opacity of the high filler content paper based on JIS P8149 is mostly 70.0% or more, and can also be 81.5% or more. Since the present invention obtains such a high filler content paper having a high opacity, it can be applied to uses such as base paper for building materials and bible paper.

[0082] The opacity of paper with a high filler content can be controlled, for example, by adjusting the content rate of filler 3 in the furnish. Among them, titanium dioxide as filler 3 has a stronger effect of improving opacity compared to other fillers 3, but due to its high price, it is likely to cause an increase in raw material costs. Therefore, from the viewpoint of suppressing an increase in the raw material costs of paper with a high filler content, it is preferable that the content rate of titanium dioxide in the furnish is small. As a method of reducing the content rate of titanium dioxide, there can be mentioned: not excessively increasing the opacity of paper with a high filler content; using a material cheaper than titanium dioxide as filler 3.

[0083] It should be noted that the filtrate turbidity based on JIS K 0101 of the white water after obtaining paper with a high filler content by the manufacturing method of the present invention is significantly reduced. As a result, the content of the filler not fixed to the pulp fibers in the white water is decreased, and thus it is possible to reduce the contamination of the paper machine and the attached equipment, and reduce the environmental load and economic load.

[0084] Examples

[0085] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these.

[0086] <Preparation of amphoteric polyacrylamide>

[0087] In a 1 L four-necked flask equipped with a stirrer and equipped with a reflux condenser tube, a dropping funnel, a thermometer, and a nitrogen inlet tube, monomers including (meth)acrylamide, an anionic vinyl monomer, and a cationic vinyl monomer, and appropriate amounts of a crosslinking agent, a chain transfer agent, a pH adjuster, and ion-exchanged water were added so that the monomer concentration reached 11% by mass. Oxygen in the solution was removed by nitrogen in the obtained monomer solution. Then, the temperature of the system was set to 60°C and stirred, and at the same time, 1 part by mass of a 2% by mass aqueous ammonium persulfate solution was added to 889 parts by mass of the monomer solution as a polymerization initiator, and then the temperature of the system was raised to 90°C and kept warm for 2 hours to polymerize the monomers, thereby preparing amphoteric polyacrylamide (polymers A to G). After the monomer polymerization was completed, 100 parts by mass of ion-exchanged water was added to the solution, and the solid content concentration was adjusted to the value shown in Table 1 to obtain an aqueous solution of amphoteric polyacrylamide.

[0088] Regarding the viscosity of the obtained aqueous solution of amphoteric polyacrylamide, the Brookfield viscosity at a liquid temperature of 25°C was measured using a Brookfield viscometer. In addition, the pH of the obtained aqueous solution of amphoteric polyacrylamide was measured using a pH meter. The results are shown in Table 1.

[0089] [Table 1]

[0090]

[0091] <Test Example 1>

[0092] [Examples 1 - 9 of the present invention]

[0093] Coniferous bleached kraft pulp and broad - leaved bleached kraft pulp were mixed at a mass ratio of 2:8, and water was added thereto to prepare a pulp slurry with a solid content concentration of 2.0% by mass. Using an experimental Niagara beater, the pulp contained in the pulp slurry was adjusted to a Canadian Standard Freeness (CSF) of 400 mL.

[0094] Next, in the furnish - making process S1, anatase titanium dioxide (pre - prepared as a slurry with a solid content of 20% by mass and waiting for use while stirring) was added to the pulp slurry as a filler at 50% by mass relative to the total mass of the solid components of the pulp fibers and fillers. Then, aluminum sulfate at 1.0% by mass relative to the total mass of the solid components of the pulp fibers and fillers and essential chemical components such as a wet - strength agent (manufactured by Kurita Water Industries Ltd., product name: Giluton WS12) were added to obtain a furnish. At this time, the mass ratio of pulp fiber to titanium dioxide was 1:1. A part of the furnish was taken out for evaluation of the filtrate turbidity.

[0095] In addition, in the amphoteric polyacrylamide addition process S2, an aqueous solution of amphoteric polyacrylamide of the type described in Table 2 among Polymers A - G was added to the furnish to form the content described in Table 2.

[0096] In addition, in the papermaking process S3, using the furnish added with the aqueous solution of amphoteric polyacrylamide, papermaking was carried out with a sheet former (model: No. 2556 - I) manufactured by KRK Kumagai Riki Kikai Co., Ltd. to obtain a wet paper with a basis weight of approximately 50 g / m 2 ². The obtained wet paper was pressed, and then dried with a drum dryer at a surface temperature of 110 °C for 90 seconds to obtain a hand - made paper (Examples 1 - 9 of the present invention). The optical properties of this hand - made paper were evaluated.

[0097] The evaluation of the filtrate turbidity of the furnish was carried out as follows: 1000 ml of the furnish that had undergone the amphoteric polyacrylamide addition process S2 was injected into a DFR - 05 device of BTG Co., and after adding the aqueous solution of amphoteric polyacrylamide at a rotational speed of 1000 rpm and at the addition amount described in Table 2, it was stirred for 40 seconds. Among them, 200 ml was collected and filtered by suction through a filter paper with a 20 - μm pore size, and 12 ml of the obtained filtrate was collected to measure the turbidity. The lower this turbidity value, the fewer the fine fibers, titanium dioxide, and other filler particles with high light - scattering ability in the filtrate, and it can be known that filler particles such as titanium dioxide are fixed to the fibers forming the paper. The results are shown in Table 2.

[0098] The evaluation of the basis weight, ash content rate in the paper, and opacity of the handmade paper was carried out after conditioning the obtained handmade paper in a thermo-hygrostat chamber at a temperature of 23°C and a relative humidity of 50% for one night. Among them, the basis weight was determined from the area and mass of the conditioned handmade paper. In addition, the measurement of the ash content rate in the paper was carried out in accordance with JIS P8251:2003. In addition, the measurement of opacity was carried out in accordance with JIS P8149:2000. The results are shown in Table 2.

[0099] [Comparative Example 1]

[0100] Except that no amphoteric polyacrylamide aqueous solution was added in the amphoteric polyacrylamide addition step S2, handmade paper was made from the furnish in the same manner as in Example 1. Then, the filtrate turbidity of the furnish and the basis weight, ash content rate in the paper, and opacity of the handmade paper were evaluated. The results are shown in Table 2.

[0101] [Comparative Example 2]

[0102] In the amphoteric polyacrylamide addition step S2, a cationic retention aid, High Holder 721 (a copolymer of acrylamide and dimethylaminoethyl acrylate, manufactured by Kurita Water Industries Ltd.), was added in the amount shown in Table 2 in place of the amphoteric polyacrylamide aqueous solution. Except for this, handmade paper was made from the furnish in the same manner as in Example 1. Then, the filtrate turbidity of the furnish and the basis weight, ash content rate in the paper, and opacity of the handmade paper were evaluated. The results are shown in Table 2.

[0103] [Comparative Example 3]

[0104] In the amphoteric polyacrylamide addition step S2, an anionic retention aid, High Holder A505 (a copolymer of acrylamide and acrylic acid, manufactured by Kurita Water Industries Ltd.), was added in the amount shown in Table 2 in place of the amphoteric polyacrylamide aqueous solution. Except for this, handmade paper was made from the furnish in the same manner as in Example 1. Then, the filtrate turbidity of the furnish and the basis weight, ash content rate in the paper, and opacity of the handmade paper were evaluated. The results are shown in Table 2.

[0105] [Table 2]

[0106]

[0107] Based on the results in Table 2, in the manufacturing methods of the high filler content papers of Examples 1 to 9 of the present invention, the conditions of the furnish preparation step (S1) and the amphoteric polyacrylamide addition step (S2) are within the appropriate range of the present invention, and the filtrate turbidity of the furnish after the amphoteric polyacrylamide addition step (S2) is 4000 NTU or less, and the ash content rate in the obtained high filler content paper is 30% or more, and the opacity is 94% or more. Therefore, the manufacturing methods of Examples 1 to 9 of the present invention obtained high filler content papers with a high ash content rate and a high opacity.

[0108] On the other hand, in the manufacturing methods of the high filler content papers of Comparative Examples 1 to 3, although the addition amount of the filler is the same as that of Examples 1 to 9 of the present invention, the conditions of the amphoteric polyacrylamide addition step (S2) are outside the appropriate range of the present invention, and at least either the ash content rate or the opacity of the obtained high filler content paper did not reach the qualified level.

[0109] <Test Example 2>

[0110] [Examples 10 to 18 of the Present Invention]

[0111] In the furnish preparation step S1, anatase titanium dioxide (previously made into a slurry with a solid content of 20% and waiting for use while stirring) is added to the pulp slurry as a filler in an amount of 30% by mass based on the total mass of the solid components of the pulp fibers and the filler. Then, aluminum sulfate in an amount of 1.0% by mass based on the total mass of the solid components of the pulp fibers and the filler, and essential pharmaceutical components such as a wet strength agent (manufactured by KURITA WATER INDUSTRIES LTD., product name: Giluton WS12) are added to obtain a furnish. At this time, the mass ratio of pulp fibers to titanium dioxide is 3:7.

[0112] In addition, for Examples 17 and 18, in the amphoteric polyacrylamide addition step S2, an aqueous solution of the amphoteric polyacrylamide of Polymer D is added to the furnish to reach the content shown in Table 3.

[0113] Except for this, in the same manner as in Examples 1 to 9, a hand sheet is made from the furnish. Then, the filtrate turbidity of the furnish and the basis weight, ash content rate in the paper, and opacity of the hand sheet are evaluated. The results are shown in Table 3.

[0114] [Comparative Example 4]

[0115] Except that no aqueous solution of amphoteric polyacrylamide is added in the amphoteric polyacrylamide addition step S2, a hand sheet is made from the furnish in the same manner as in Example 10. Then, the filtrate turbidity of the furnish and the basis weight, ash content rate in the paper, and opacity of the hand sheet are evaluated. The results are shown in Table 3.

[0116] [Comparative Example 5]

[0117] In the amphoteric polyacrylamide addition step S2, instead of the amphoteric polyacrylamide aqueous solution, a cationic retention aid, High Holder 721 (a copolymer of acrylamide and dimethylaminoethyl acrylate, manufactured by Kurita Water Industries Ltd.), was added in the addition amounts shown in Table 3. Otherwise, a handsheet was made from the furnish in the same manner as in Example 10. Then, the filtrate turbidity of the furnish, the basis weight of the handsheet, the ash content in the paper, and the opacity were evaluated. The results are shown in Table 3.

[0118] [Comparative Example 6]

[0119] In the amphoteric polyacrylamide addition step S2, instead of the amphoteric polyacrylamide aqueous solution, an anionic retention aid, High Holder A505 (a copolymer of acrylamide and acrylic acid, manufactured by Kurita Water Industries Ltd.), was added in the addition amounts shown in Table 3. Otherwise, a handsheet was made from the furnish in the same manner as in Example 10. Then, the filtrate turbidity of the furnish, the basis weight of the handsheet, the ash content in the paper, and the opacity were evaluated. The results are shown in Table 3.

[0120] [Table 3]

[0121]

[0122] According to the results in Table 3, in the methods for manufacturing high - filler - content paper of Invention Examples 10 to 18 of the present invention, the conditions of the furnish preparation step (S1) and the amphoteric polyacrylamide addition step (S2) are within the appropriate range of the present invention. After the amphoteric polyacrylamide addition step (S2), the filtrate turbidity of the furnish is 2000 NTU or less, the ash content in the obtained high - filler - content paper is 18% or more, and the opacity is 81.5% or more. Therefore, the manufacturing methods of Invention Examples 10 to 18 of the present invention yield high - filler - content paper with a high ash content and high opacity.

[0123] On the other hand, in the methods for manufacturing high - filler - content paper of Comparative Examples 4 to 6, although the addition amount of the filler is the same as that in Invention Examples 10 to 18 of the present invention, the conditions of the amphoteric polyacrylamide addition step (S2) are outside the appropriate range of the present invention, and at least one of the ash content and the opacity of the obtained high - filler - content paper does not reach the qualified level.

[0124] <Test Example 3>

[0125] [Invention Examples 19 - 27]

[0126] In the stock preparation process S1, anatase titanium dioxide (previously prepared as a slurry with a solid content of 20% by mass and stirred and waiting for use) is added to the pulp slurry as a filler in an amount of 12% by mass based on the total mass of the solid components of the pulp fibers and fillers. Subsequently, aluminum sulfate in an amount of 1.0% by mass based on the total mass of the solid components of the pulp fibers and fillers, and essential chemical components such as a wet strength agent (manufactured by Kurita Water Industries, product name: Giluton WS12) are added to obtain the stock. At this time, the mass ratio of pulp fibers to titanium dioxide is 12:88.

[0127] In addition, regarding Examples 26 and 27, in the amphoteric polyacrylamide addition process S2, an aqueous solution of the amphoteric polyacrylamide of Polymer G is added to the stock to reach the content described in Table 4.

[0128] Except for the above, in the same manner as in Examples 1 to 9, a hand sheet is made from the stock. Then, the filtrate turbidity of the stock, the basis weight of the hand sheet, the ash content rate in the paper, and the opacity are evaluated. The results are shown in Table 4.

[0129] [Comparative Example 7]

[0130] Except that the aqueous solution of amphoteric polyacrylamide is not added in the amphoteric polyacrylamide addition process S2, a hand sheet is made from the stock in the same manner as in Example 19. Then, the filtrate turbidity of the stock, the basis weight of the hand sheet, the ash content rate in the paper, and the opacity are evaluated. The results are shown in Table 4.

[0131] [Comparative Example 8]

[0132] In the amphoteric polyacrylamide addition process S2, a cationic retention aid High Holder 721 (a copolymer of acrylamide and dimethylaminoethyl acrylate, manufactured by Kurita Water Industries) is added in the addition amount described in Table 4 in place of the aqueous solution of amphoteric polyacrylamide. Except for the above, a hand sheet is made from the stock in the same manner as in Example 19. Then, the filtrate turbidity of the stock, the basis weight of the hand sheet, the ash content rate in the paper, and the opacity are evaluated. The results are shown in Table 4.

[0133] [Comparative Example 9]

[0134] In the amphoteric polyacrylamide addition process S2, an anionic retention aid High Holder A505 (a copolymer of acrylamide and acrylic acid, manufactured by Kurita Water Industries) is added in the addition amount described in Table 4 in place of the aqueous solution of amphoteric polyacrylamide. Except for the above, a hand sheet is made from the stock in the same manner as in Example 19. Then, the filtrate turbidity of the stock, the basis weight of the hand sheet, the ash content rate in the paper, and the opacity are evaluated. The results are shown in Table 4.

[0135] [Table 4]

[0136]

[0137] According to the results in Table 4, in the method for manufacturing high filler content paper in Examples 19 to 27 of the present invention, the conditions of the furnish preparation step (S1) and the amphoteric polyacrylamide addition step (S2) are within the appropriate range of the present invention, and the filtrate turbidity of the furnish after the amphoteric polyacrylamide addition step (S2) is 1000 NTU or less, and the ash content rate in the obtained high filler content paper is 8.5% or more, and the opacity is 70% or more. Therefore, the manufacturing methods of Examples 19 to 27 of the present invention obtain high filler content paper with a high ash content rate and a high opacity.

[0138] On the other hand, in the methods for manufacturing high filler content paper in Comparative Examples 7 to 9, although the addition amount of the filler is the same as that in Examples 19 to 27 of the present invention, the conditions of the amphoteric polyacrylamide addition step (S2) are outside the appropriate range of the present invention, and at least any one of the ash content rate and the opacity of the obtained high filler content paper does not reach the qualified level.

[0139] From the above, it can be seen that according to the method for manufacturing high filler content paper of the present invention, compared with the method of the comparative example with the same addition amount of the filler containing titanium dioxide, it is possible to obtain paper with a high ash content rate and a high opacity, and moreover, the outflow ratio of the filler flowing out into the white water is small.

[0140] Explanation of reference numerals

[0141] 1, 9 Furnish

[0142] 2 Amphoteric polyacrylamide

[0143] 3 Filler

[0144] 4 Pulp fiber

[0145] 5 Retention aid

[0146] S1 Furnish preparation step

[0147] S11 Amphoteric polyacrylamide preparation step

[0148] S2 Amphoteric polyacrylamide addition step

[0149] S3 Papermaking step

Claims

1. A method for manufacturing a paper with a high filler content, which includes: A papermaking stock preparation process for preparing a papermaking stock by adding a filler containing titanium dioxide to a pulp slurry; An amphoteric polyacrylamide addition step of adding amphoteric polyacrylamide to the papermaking stock in a range of 0.005% by mass or more and 3% by mass or less based on the total mass of the solid components of the pulp fibers and the filler; and, A papermaking step of making paper from the papermaking stock to which the amphoteric polyacrylamide has been added, wherein, in the papermaking stock obtained by the papermaking stock preparation process, based on the total mass of the solid components of the pulp fibers and the filler, the content rate of the titanium dioxide is 1% by mass or more, and the content rate of the filler containing the titanium dioxide is in a range of 8.5% by mass or more and 50% by mass or less.

2. The method for manufacturing a paper with a high filler content according to claim 1, wherein, In the papermaking stock preparation process, aluminum sulfate is further added in a range of 0.5% by mass or more and 10% by mass or less based on the total mass of the solid components of the pulp fibers and the filler.

3. The method for manufacturing a paper with a high filler content according to claim 1 or 2, which further includes before the step of adding amphoteric polyacrylamide: An amphoteric polyacrylamide production process for producing the amphoteric polyacrylamide by polymerizing monomers in an aqueous medium, wherein the monomers contain, relative to the total molar sum: (meth)acrylamide in a range of 60 mol% or more and 98 mol% or less, an anionic vinyl monomer in a range of 1 mol% or more and 39 mol% or less, and a cationic vinyl monomer in a range of 1 mol% or more and 39 mol% or less.

4. The method for manufacturing a paper with a high filler content according to any one of claims 1 to 3, wherein, The Brookfield viscosity of the amphoteric polyacrylamide produced by the amphoteric polyacrylamide production process is in a range of 1000 cps or more and 20000 cps or less when the solid component concentration is set to 10% by mass.

5. The method for manufacturing a paper with a high filler content according to any one of claims 1 to 4, wherein, The ash content rate of the paper with a high filler content is in a range of 8.5% by mass or more and 50% by mass or less.

Citation Information

Patent Citations

  • papermaking

    JP1997195197A

  • Method for making paper

    JP2003089994A

  • Filler-containing paper, and method for producing filler-containing paper

    JP2005171411A